Theoretical and Conceptual Perspectives in Social Research Methods: A Guide to Students and Researchers. By Dr. Birpal Singh Thenua. Agra, Social Development Federation, 2024. 444p. ISBN: 978-81-968705-2-2. Price: 39.50. - Singh, B.P. (Access: An International Journal of Nepal Library Association, 2025)
Not available